Selective binding of looped oligonucleotides to a single-stranded DNA and its influence on replication in vitro. - Azhayeva, E (1995)
Complexing of looped and circular oligonucleotides, composed of either 2'-deoxyribo- or 2'-O-methylribonucleoside units, with completely matching or partially mismatching complementary DNA sequences was studied. Melting experiments revealed considerable differences among the stabilities of these hybrid complexes. Maximum stability and selectivity was displayed by oligomers 2 and 5. It was concluded that a linear stretch, attached to 1'-O- of 3'-deoxypsicothymidine unit (Z) increases the selectivity of hybridisation and stability of the complex as a whole. This allows one to aim the target DNA very precisely at its polyadenine part as well as at adjacent sequence simultaneously. Experiments on termination of primer extension catalysed by different DNA-polymerases--Sequenase, Klenow fragment and Tth--have demonstrated that looped oligomer 5, composed of 2'-O-methylribonucleosides appears to be a highly selective and potent inhibitor of replication in vitro. Features of looped oligonucleotides, composed of 2'-O-methylribonucleosides seem to be useful for design of highly specific antigene oligonucleotides.